Summary of the Workshop on Consumer Behavior and Payment Choice - Scott Schuh; Joanna Stavins (Federal Reserve Bank of Boston, 2008)
This paper summarizes and outlines some interesting issues that arose during a recent workshop on Consumer Behavior and Payment Choice, hosted by the Federal Reserve Bank of Boston's Emerging Payments Research Group (EPRG) on July 25, 2008. Topics addressed are the consumer adoption of new payment technologies, credit card debt management, payment card surcharges, and involuntary bank account closures.
Keywords: D13; D14; E41; G11; 330; Zahlungsverkehr; Bargeldloser Zahlungsverkehr; Innovationsdiffusion; Konsumentenverhalten; USA